ANALISIS KESANTUNAN BERBAHASA DALAM NOVEL ARAH LANGKAH KARYA FIERSA BESARI - Annur, Dedy Setiadi; Patriantoro, Patriantoro; Madeten, Sisilya (Universitas Tanjungpura, 2025)
This research seeks to explain the principles of compliance and violation of language politeness contained in the novel Arah Langkah by Fiersa Besari based on Leech's theory. In addition, this study also describes the implications of language politeness in learning Indonesian in high school. The form of research used is qualitative descriptive research that seeks to characterize the language politeness both obeying and violating the maxims of politeness in the novel Arah Langkah. The technique used in collecting data is a documentary study, after the data is collected, the author describes the data and then analyzes it to obtain conclusions. The findings in this study show that the language politeness used is quite high, as evidenced by the data on the compliance of language politeness which is higher than the violation. The data findings of politeness maxim compliance amounted to 32 utterances, while the violation data amounted to 5 utterances. This research can be implied in Indonesian language learning on negotiation text material by paying attention to polite word selection. The novel Arah Langkah can serve as an illustration for educators. of a novel that pays attention to the use of polite language in learning, in order to help the expected learning objectives.